A new model to enhance the QoS of spectral amplitude coding-optical code division multiple access system with OFDM technique - Aldhaibani, A.O.; Rahman, T.A.; Aljunid, S.A.; Hindia, M.N.; Hanafi, Effariza (Springer, 2016)
A new optical orthogonal frequency division multiplexing technique with spectrum amplitude coding optical code division access (SAC-OCDMA) system is developed to enhance the channel data rate, reduce power, and increase the number of SAC-OCDMA system users. The average received signal-to-noise ratio with inter-modulation distortion of subcarriers is derived. Theoretical results are evaluated based on bit error rate, number of users, data rate, and amount of power saved. The proposed system is then compared with the traditional hybrid sub-carrier multiplexing (SCM)/SAC OCDM. The results show that the proposed system reduces approximately −8 dBm of power and doubles the number of users at a higher data rate than the SCM/SAC-OCDMA system. Proof-of-principle simulations of the proposed system are successfully implemented. Overall, the proposed system performed better than the SCM/SAC-OCDMA system. The system is designed based on modified double weight code, which provides better performance than Hadamard and modified frequency-hopping codes.